Analisis Perbandingan Hasil Simulasi Dosis Serap Kanker Payudara Pada Wanita Dalam Brakiterapi Dengan Pd-103 Dan I-125 Menggunakan MCNP - Matius M.L.T; Agnes Yulia B (Publikasi dan UKI Press UKI Toraja., 2022)
Brachytherapy that known as internal radiotherapy is a radiotherapy that increasingly being used to kill cancer cells by inserting or implanting a radiation source into the tissue of the organ that is attacked by cancer cells. Currently, the method of brachytherapy by implanting permanent implants is widely used, especially using Pd-103 and I-125 sources. In radiation therapy process, absorbed dose is one of the most important parameter so that a simulation before radiation therapy is very important. The purpose of this study was to analyze the results of the calculation of the simulated absorption dose in brachytherapy between Pd-103 and I-125. The simulations are carried out using MCNP in which the geometry of the breast, cancer cells and radioactive source is defined as a sphere with a breast diameter is 10 cm, the diameter of cancer cells is 2.5 cm, and the radioactive diameter is 0.7 cm. Variance of total seed, and distance between the source and cancer cells will be input to see how its effect the absorbed dose.